2005
DOI: 10.1161/01.cir.0000153270.25541.72
|View full text |Cite
|
Sign up to set email alerts
|

Role of β 2 Adrenergic Receptors in Human Atherosclerotic Coronary Arteries

Abstract: Background-Adrenergic regulation of coronary vasomotion is balanced between ␣ 1 -adrenergic-mediated (␣ 1 -AR) constriction and ␤ 2 -adrenergic-mediated (␤ 2 -AR) relaxation. This study aimed at assessing the role of ␤ 2 -ARs in normal, mildly atherosclerotic, and stenotic human coronary arteries. Methods and Results-During intracoronary (IC) infusion of increasing doses of the ␤ 2 -AR agonist salbutamol (0.15, 0.3, and 0.6 g/min) and the endothelial vasodilator acetylcholine (1, 3, and 10 g/min), we measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 38 publications
3
59
0
Order By: Relevance
“…30 A recent study found the effects of acetylcholine and the ␤-2 agonist salbutamol to be similar when given locally in the coronary arteries. 31 …”
Section: Relationships Between the Methodsmentioning
confidence: 99%
“…30 A recent study found the effects of acetylcholine and the ␤-2 agonist salbutamol to be similar when given locally in the coronary arteries. 31 …”
Section: Relationships Between the Methodsmentioning
confidence: 99%
“…Alterations in autonomic tone, mediated by impairment of coronary β 2 -adrenergic receptor response during sympathetic activation, may cause vasoconstriction [4]. Moreover, smooth muscle hyper-contractility and infl ammation, as well as allergic responses, are supposed to be possible but not clearly demonstrated vasoconstriction mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function plays important role in β2-agonist effect on vascular tone. Intracoronary infusion of salbutamol induces vasoconstriction in stenotic coronary arteries without increase in heart rate and blood pressure [8]. Underlying endothelial dysfunction was likely a reason for our patient to develop coronary spasm in response to albuterol and dobutamine combination since she had no obstructive coronary disease.…”
Section: Discussionmentioning
confidence: 99%